Chewa Rainmaking Beliefs and the Dutch Reformed Missionaries in Central Malawi, 1889-1905 - Mbaya, Henry; Mbaya, Thokozile J. (African historical review, 2024)
28 November 1889 marked the first encounter between the Dutch Reformed missionaries from South Africa and the Chewa society at Chiwere village in central Malawi. The encounter took place during a drought, and the missionaries were challenged to pray for rain. This article discusses the significance of the encounter in terms of the religious powers represented by Reformed Christianity through the agency of missionaries, and Chewa religious and cultural beliefs through the agency of rainmakers. The article shows that the missionaries' interventions and teachings undermined the Chewa rain-related belief systems. Finally, the article argues that the missionaries' conversion of Chauwa at Nkhoma considerably undermined the Chewa religious system to the extent that it provoked resistance from some Chewa people.